2015
DOI: 10.1016/j.adengl.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Reaction to Antituberculosis Therapy in a Patient With Lupus Vulgaris

Abstract: Patients receiving treatment for tuberculosis may experience an unexpected deterioration of their disease; this is known as a paradoxical reaction. We present the case of a 59-year-old man with lupus vulgaris who experienced a paradoxical deterioration of cutaneous lesions after starting antituberculosis therapy. The reaction was self-limiting; the lesions gradually improved, and the final outcome was very good. Paradoxical reactions are well-known in patients with human immunodeficiency virus (HIV) infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Besides, it should also be noted that Santesteban et al reported a case of paradoxical responses during treatment of lupus vulgaris. 17 Our experience in this case shows that even for such patients with huge and atypical skin lesions on the premise of long-term application of glucocorticoids and immunosuppressants and negative results of T-SPOT.TB, the application of traditional antituberculosis treatment is still effective.…”
Section: Discussionmentioning
confidence: 73%
“…Besides, it should also be noted that Santesteban et al reported a case of paradoxical responses during treatment of lupus vulgaris. 17 Our experience in this case shows that even for such patients with huge and atypical skin lesions on the premise of long-term application of glucocorticoids and immunosuppressants and negative results of T-SPOT.TB, the application of traditional antituberculosis treatment is still effective.…”
Section: Discussionmentioning
confidence: 73%